A mouse model of brittle cornea syndrome caused by mutation in Zfp469 - Chloe M. Stanton; Amy S. Findlay; Camilla Drake; Mohammad Z. Mustafa; Philippe Gautier; Lisa McKie; Ian J. Jackson; Veronique Vitart (The Company of Biologists, 2021)
Brittle cornea syndrome (BCS) is a rare recessive condition characterised by extreme thinning of the cornea and sclera. BCS results from loss-of-function mutations in the poorly understood genes ZNF469 or PRDM5. In order to determine the function of ZNF469 and to elucidate pathogenic mechanisms, we used genome editing to recapitulate a human ZNF469 BCS mutation in the orthologous mouse gene Zfp469. Ophthalmic phenotyping showed that homozygous Zfp469 mutation causes significant central and peripheral corneal thinning arising from reduced stromal thickness. Expression of key components of the corneal stroma in primary keratocytes from Zfp469BCS/BCS mice is affected, including decreased Col1a1 and Col1a2 expression. This alters the collagen type I/collagen type V ratio and results in collagen fibrils with smaller diameter and increased fibril density in homozygous mutant corneas, correlating with decreased biomechanical strength in the cornea. Cell-derived matrices generated by primary keratocytes show reduced deposition of collagen type I, offering an in vitro model for stromal dysfunction. Work remains to determine whether modulating ZNF469 activity will have therapeutic benefit in BCS or in conditions such as keratoconus in which the cornea thins progressively. This article has an associated First Person interview with the first author of the paper.